I Wonder Why Snakes Shed Their Skin - O'Neill, Amanda; Nang Chan Yeema (New York, USA Southwestern Company, 1997)
Answers such questions about reptiles as why do snakes stare, are frogs and newts reptiles and which reptile lives longest.
Keywords: Juvenile Nonfiction